Excitable Adult-Generated GABAergic Neurons Acquire Functional Innervation in the Cortex after Stroke - Kannangara, Timal S. (Stem Cell Reports, 2018)
Ischemic stroke enhances the proliferation of adult-generated precursor cells that ectopically migrate toward the infarct. Studies have correlated precursor cell proliferation and subsequent adult neurogenesis with enhanced stroke recovery, yet it remains unclear whether stroke can generate new neurons capable of functional integration into the injured cortex. Here, using single and bitransgenic reporter mice, we identify spatial and temporal features of a multilineage cellular response to focal ischemia. We reveal that a small population of stroke-induced immature neurons accumulate within the peri-infarct region of the adult sensorimotor cortex, exhibit voltage-dependent conductances, fire action potentials, express GABAergic markers, and receive sparse GABAergic synaptic inputs. Collectively, these findings reveal that GABAergic neurons arising from the lateral ventricle have the capacity to integrate into the stroke-injured cortex, although their limited number and exiguous synaptic integration may limit their ability to participate in stroke recovery.